2015
DOI: 10.1038/emi.2015.30
|View full text |Cite
|
Sign up to set email alerts
|

Is mother-to-infant transmission the most important factor for persistent HBV infection?

Abstract: Of the infants born to hepatitis B surface antigen (HBsAg)-positive mothers globally, 42.1% who did not receive hepatitis B virus (HBV) passive-active immunoprophylaxis and 2.9% of infants who received the immunoprophylaxis acquired HBV infection perinatally. Moreover, perinatal infection occurred in 84.2% (18.8%–100%) and 8.7% (0.0–21.0%) of infants born to hepatitis B e-antigen (HBeAg)-positive mothers who did not and did receive immunoprophylaxis, respectively; by contrast, the infection rates were 6.7% (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
65
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 91 publications
3
65
0
1
Order By: Relevance
“…The polymorphic genotypes that are significantly association with increased risks of chronic progression of HBV infection as well as immune selection of the end-stage liver diseases-associated HBV mutations are more frequent in the Han Chinese than in European populations. These data indicate that the Han Chinese are inherently more apt to progressing into chronic infection once exposed to HBV infection than European, whereas European tend to recover from HBV infection spontaneously [12] . This might be one of the reasons why chronic HBV infection and the HBVinduced end-stage liver diseases are more frequent in Chinese than in European populations.…”
mentioning
confidence: 80%
See 3 more Smart Citations
“…The polymorphic genotypes that are significantly association with increased risks of chronic progression of HBV infection as well as immune selection of the end-stage liver diseases-associated HBV mutations are more frequent in the Han Chinese than in European populations. These data indicate that the Han Chinese are inherently more apt to progressing into chronic infection once exposed to HBV infection than European, whereas European tend to recover from HBV infection spontaneously [12] . This might be one of the reasons why chronic HBV infection and the HBVinduced end-stage liver diseases are more frequent in Chinese than in European populations.…”
mentioning
confidence: 80%
“…Several longitudinal studies carried in China have also demonstrated that baseline A1762T/G1764A mutation increases the risk of HCC in chronic HBV carriers or CHB patients [34][35][36][37] . Among the HCC-risk HBV mutations, the A1762T/G1764A is usually detected in the early stage in young adolescents, while other mutations including T1753V, C1653T, G1899A, and preS deletion appear only at the late stage of chronic HBV infection [12,38] . Reaction to chronic HBV infection, as characterized by immune response-induced hepatocyte damage and release of transaminase, facilitates the generation of the HBV mutations, indicating active immune selection of the HBV mutants during HBeAg seroconversion from HBeAg-positive to HBeAg-negative.…”
Section: "Dead-end" Evolution Of Hbvmentioning
confidence: 99%
See 2 more Smart Citations
“…The exact mechanism by which HBV enters the fetus through the maternal placenta remains unclear. The HBsAg is detectable in amniotic fluid, cord blood, breast milk, vaginal fluid, and infant gastric contents, suggesting multiple routes for MTCT [4,5].…”
Section: Introductionmentioning
confidence: 99%